Eficácia da pré-medicação com um anti-inflamatório não-esteroidal no sucesso da anestesia de molares inferiores com pulpite aguda irreversível - Paredes, Maria Jose Zumarraga (2018)
The aim of this study is to evaluate the administration action, prior to endodontic treatment, of a non-steroidal anti-inflammatory drug (Voltaren Retard®) for anesthetic effectiveness in lower molars with acute irreversible pulpitis. We selected 20 patients distributed in two experimental groups (placebo and experimental). Before received the treatment, patientsqualify their pain intensity with the help of a visual analogue scale (VAS). In addition, 30 minutes prior to treatment, patients either received a placebo pill or Voltaren Retard® 100 mg. Subsequently, patients were anesthetized using the inferior alveolar nerve block, infiltration of the buccal nerve and intra-ligament techniques. After anesthesia is confirmed, by cold testing and VAS scale. The coronary opening and pulp removal were performed, filling the VAS scale. ANOVA e Tukey (p≤0.05)were applied. The results showed that 70% of patients who used Voltaren Retard 100 mg get absence pain during instrumentation, differently from the placebo group, who obtained 30% of patients (p≤0.001). Therefore, the drug association with an anesthetic technique benefits the treatment of acute irreversible pulpitis.